Correlating nanoscale secondary ion mass spectrometry and atom probe tomography analysis of uranium enrichment in metallic nuclear fuel. Issue 1 (9th November 2020) - Kautz, Elizabeth; Cliff, John; Lach, Timothy; Reilly, Dallas; Devaraj, Arun
Abstract : 235 U enrichment in a metallic nuclear fuel was measured via NanoSIMS and APT, allowing for a direct comparison of enrichment across length scales and resolutions. Abstract : Accurate measurements of 235 U enrichment within metallic nuclear fuels are essential for understanding material performance in a neutron irradiation environment, and the origin of secondary phases ( e.g. uranium carbides). In this work, we analyse 235 U enrichment in matrix and carbide phases in low enriched uranium alloyed with 10 wt% Mo via two chemical imaging modalities—nanoscale secondary ion mass spectrometry (NanoSIMS) and atom probe tomography (APT). Results from NanoSIMS and APT are compared to understand accuracy and utility of both approaches across length scales. NanoSIMS and APT provide consistent results, with no statistically significant difference between nominal enrichment (19.95 ± 0.14 at% 235 U) and that measured for metal matrix and carbide inclusions.